Radicicol-Mediated Inhibition of Topoisomerase VIB-VIA Activity of the Human Malaria Parasite Plasmodium falciparum - Chalapareddy, Sureshkumar (mSphere, 2016)
Plasmodium falciparum topoisomerase VIB (TopoVIB)-TopoVIA (TopoVIB-VIA) complex can be potentially exploited as a drug target against malaria due to its absence from the human genome. Previous work in our laboratory has suggested that P. falciparum TopoVIB (PfTopoVIB) might be a target of radicicol since treatment of parasite cultures with this antibiotic is associated with upregulation of Plasmodium TopoVIB at the transcript level as well as at the protein level. Further studies demonstrated that radicicol treatment impaired mitochondrial replication of human malaria parasite P. falciparum. However, the technical challenge associated with the expression of the above protein complex hampered its functional characterization. Using Saccharomyces cerevisiae as a heterologous system, we expressed PfTopoVIB (Myc-tagged) and PfTopoVIA (Flag-tagged) (PfTopoVIB-VIA) proteins. Yeast two-hybrid analysis showed the formation of PfTopoVIB homodimers and PfTopoVIB/PfTopoVIA heteromers. Our study demonstrated that PfTopoVIB and PfTopoVIA together can rescue the lethal phenotype of yeast ΔtopoII mutants, whereas Plasmodium topoisomerase VIB alone cannot. Using yeast cell-free extracts harboring the PfTopoVIB-VIA protein complex, we have performed a decatenation assay and observed that PfTopoVIB-VIA can decatenate DNA in an ATP- and Mg(2+)-dependent manner. The specificity of this enzyme is established by abrogation of its activity in the presence of PfTopoVIB-specific antibody. Our study results show that radicicol and etoposide can specifically inhibit PfTopoVIB-VIA decatenation activity whereas the gyrase inhibitor novobiocin cannot. Such a yeast-based assay system can be employed in screening specific inhibitors against Plasmodium VIB-VIA. IMPORTANCE In this study we characterize topoisomerase VI from Plasmodium falciparum using genetic and biochemical approaches. We use various inhibitors and identify radicicol as a specific inhibitor of its decatenation activity. We establish a very simple and economical biochemical assay system that can be exploited to screen inhibitors of PfTopoVI.